2010
DOI: 10.1016/j.devcel.2010.01.016
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin Activity in the Dermal Papilla Regulates Morphogenesis and Regeneration of Hair

Abstract: SUMMARY The activity of keratinocytes in the hair follicle is regulated by signals from a specialized mesenchymal niche, the dermal papilla. Here, mice expressing cre recombinase in the dermal papilla were developed to probe the interaction between follicular keratinocyte populations and the dermal papilla in vivo. Inactivation of the β-catenin gene within the dermal papilla of fully developed hair follicles results in dramatically reduced proliferation of the progenitors and their immediate progeny that gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
355
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(376 citation statements)
references
References 42 publications
18
355
0
3
Order By: Relevance
“…In contrast to the germline Bmal1 deletion, delayed anagen progression is not observed in mice with keratinocyte-specific deletion of Bmal1, indicating that in regulating this process BMAL1 acts either through the central clock, possibly through endocrine signaling, or through nonkeratinocyte cell types in the skin such as the dermal papilla (24) or preadipocytes (25), both of which have been shown to play a critical role in anagen initiation. Although a recent study showed that keratinocyte-specific deletion of Bmal1 altered the population size of bulge cells in the activation-ready state (12), this study also did not report delayed anagen initiation.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast to the germline Bmal1 deletion, delayed anagen progression is not observed in mice with keratinocyte-specific deletion of Bmal1, indicating that in regulating this process BMAL1 acts either through the central clock, possibly through endocrine signaling, or through nonkeratinocyte cell types in the skin such as the dermal papilla (24) or preadipocytes (25), both of which have been shown to play a critical role in anagen initiation. Although a recent study showed that keratinocyte-specific deletion of Bmal1 altered the population size of bulge cells in the activation-ready state (12), this study also did not report delayed anagen initiation.…”
Section: Discussionmentioning
confidence: 86%
“…FACS-isolated DP cells rapidly lose their inductive properties upon in vitro culture, which can be rescued by addition of Wnt3a (Kishimoto et al 2000). b-Catenin deletion specifically in DP cells results in a strong decrease in HF progenitor proliferation and HF terminal differentiation, leading to a premature entry in catagen and preventing bulge SCs from reinitiating a novel cycle of HF regeneration (Enshell-Seijffers et al 2010). In adult epidermis, b-catenin regulates the expression of nephronectin by HF SCs, which in turn regulates the attachment of the arrector pili muscle to the top of the bulge (Fujiwara et al 2011).…”
Section: Hf Morphogenesis and Cyclingmentioning
confidence: 99%
“…Robust TGF-b and Bmp signals act as 'activation breaks', rendering bulge cells dormant during the resting phase of the hair cycle (telogen) [9][10][11] . At the onset of the growth phase (anagen), bulge cells respond to Wnt signals by migrating into the lower proliferative hair germ region, where they contribute to follicle growth [12][13][14][15] . Subsequently, at mid-anagen, the bulge undergoes a second round of activation, which replenishes cells lost at the onset of anagen 2,3 .…”
mentioning
confidence: 99%